2017
DOI: 10.1103/physrevmaterials.1.061002
|View full text |Cite
|
Sign up to set email alerts
|

One-dimensional phosphorus chain and two-dimensional blue phosphorene grown on Au(111) by molecular-beam epitaxy

Abstract: Single layer (SL) phosphorus (phosphorene) has drawn considerable research attention recently as a two-dimensional (2D) material for application promises. It is a semiconductor showing superior transport and optical properties. Few-layer or SL black phosphorus has been successfully isolated by exfoliation from bulk crystals and extensively studied thereof for its electronic and optical properties. Blue phosphorus (blueP), an allotrope of black phosphorus where atoms are arranged in a more flat atomic configura… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(60 citation statements)
references
References 39 publications
2
58
0
Order By: Relevance
“…Various 2D materials, such as graphene, GaSe, HfSe 2 /MoSe 2 , and MoTe 2 /MoS 2 , have been synthesized by MBE method. Specifically, 2D group‐VA materials, such as β‐phosphorene, α‐antimonene, β‐antimonene, and β‐bismuthene, have been reported to be successfully grown by MBE method. Through reflection high‐energy electron diffraction (RHEED) monitoring, the thickness of layers can be controlled precisely, making MBE a promising method for synthesizing 2D materials.…”
Section: Realizing 2d V‐v Binary Materialsmentioning
confidence: 99%
“…Various 2D materials, such as graphene, GaSe, HfSe 2 /MoSe 2 , and MoTe 2 /MoS 2 , have been synthesized by MBE method. Specifically, 2D group‐VA materials, such as β‐phosphorene, α‐antimonene, β‐antimonene, and β‐bismuthene, have been reported to be successfully grown by MBE method. Through reflection high‐energy electron diffraction (RHEED) monitoring, the thickness of layers can be controlled precisely, making MBE a promising method for synthesizing 2D materials.…”
Section: Realizing 2d V‐v Binary Materialsmentioning
confidence: 99%
“…72 Similar effects have been found for a 1D structure of phosphorus on the Au(111) surface, whereby the formation of the well-defined zigzag chain was hindered. 34 It is therefore important to know whether the properties predicted above for the free-standing chains can be modified when they are grown on specific substrates. To this end, we first examined zigzag monatomic chains placed on their parent 2D monolayers in hexagonal buckled honeycomb (hb) structures; namely P-ZZ on blue phosphorene, As-ZZ on hb-arsenene, Sb-ZZ on hb-antimonene and Bi-ZZ on hb-bismuthenene.…”
Section: Zigzag Chains Supported By Substratesmentioning
confidence: 99%
“…33 At the same time, Xu et al reported that an ordered 1D structure of adsorbed phosphorus atoms can grow at low coverage on Au(111) through the molecular-beam epitaxy method. 34 The formation of a well-defined zigzag chain is hindered by the strong interaction between P adatoms and Au atoms of the substrate. Bismuth dimers in the nanoline are observed experimentally on the Si(001) surface, 35 or on H passivated Si(100) surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these allotropes are semiconducting with bandgap ranging from 0.48 eV for ε-phosphorene to 2.09 eV for octa-phosphorene [17]. Out of all these allotropes, only α-and β-phosphorene have been experimentally realized [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%